Designing Quality Management Systems for Higher Education Transformation - Yusup, Muhammad Firdaus Bin (Journal of Strategy and Transformation in Educational Management, 2025)
Higher education institutions are undergoing significant transformation driven by rapid digitalization, shifting learner expectations, and rising demands for accountability. These changes challenge universities to redesign their Quality Management Systems (QMS) so they can remain agile, competitive, and aligned with global standards. This study presents a strategic framework for designing a QMS that supports institutional transformation by integrating digital tools, evidence-based decision-making, and continuous quality improvement processes. Using a qualitative exploratory approach involving document analysis and expert validation, the study identifies key components of an effective QMS: leadership commitment, holistic governance, digital monitoring systems, stakeholder engagement, and data-driven evaluation. Findings show that well-structured QMS designs lead to improved institutional performance, enhanced academic quality, and sustainable organizational transformation. The paper offers practical implications for higher education leaders seeking to strengthen internal quality assurance, optimize strategic decision-making, and create a culture of continuous improvement.